2010
DOI: 10.1007/7854_2010_57
|View full text |Cite
|
Sign up to set email alerts
|

Models of Neurodevelopmental Abnormalities in Schizophrenia

Abstract: The neurodevelopmental hypothesis of schizophrenia asserts that the underlying pathology of schizophrenia has its roots in brain development and that these brain abnormalities do not manifest themselves until adolescence or early adulthood. Animal models based on developmental manipulations have provided insight into the vulnerability of the developing fetus and the importance of the early environment for normal maturation. These models have provided a wide range of validated approaches to answer questions reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 345 publications
(502 reference statements)
2
43
1
Order By: Relevance
“…Cognitive deficits are at the core of schizophrenia, including difficulties in problem solving, social cognition, and working memory (Powell, 2010). Therefore, rodent models have focused on tasks associated with learning and memory, working memory, and cognitive flexibility.…”
Section: Animal Models Of a Noisy Brainmentioning
confidence: 99%
“…Cognitive deficits are at the core of schizophrenia, including difficulties in problem solving, social cognition, and working memory (Powell, 2010). Therefore, rodent models have focused on tasks associated with learning and memory, working memory, and cognitive flexibility.…”
Section: Animal Models Of a Noisy Brainmentioning
confidence: 99%
“…We can only comment selectively on this extensive literature; more comprehensive reviews can be found elsewhere (e.g. Powell, 2010; Powell and Geyer, 2002; Powell et al, 2009, 2012; Swerdlow et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…The terms isolation rearing or isolation housing are commonly used to denote social isolation of adolescent (post-weaning) or adult rats, respectively. The consequences of isolation are more severe in rats compared with other rodent species (Einon et al, 1981) and it has been argued that social isolation of rats has a good etiological validity to model human mental illness (Powell, 2010; CzĂ©h et al, 2016). Given the emerging important role of BDNF in stress-related mental disorders, the aim of our investigation was to systematically summarize current evidence for altered BDNF signaling in experimental studies employing chronic social isolation of rats.…”
Section: Introductionmentioning
confidence: 99%